Laien als Experten und Experten als Laien.: Zur Problematik eines etablierten Begriffspaares - Hoffmeister, Toke (Linguistik Online, 2019)
This paper elaborates on the problem of the traditional terms of experts and lay people. Language is a fundamental component of everyday life and all individuals react to language issues by using language itself. The paper contests the claim that lay people do not exist in the field of linguistics. There must be dealt with innovative concepts, such as professional and amateur, because the “lay people” (as a considerable amount of studies have investigated) are well aware of processes concerning language issues and thus generate their own kind of “linguistic theory”. The task of linguists is to scrutinize such theories, which form the basis for the understanding of linguistic change and the formation of language norms. The line of argument presented here is arranged in chronological order: starting in antiquity, light will be shed on the meaning of the term “lay people” in cultural history. Special emphasis will be put on the Middle Ages, the early modern age and the modern period.